Why do infants pull their ears?. Issue 5 (October 2019) - Cakabay, Taliye; Üstün Bezgin, Selin; Tarakcioglu, Mahmut Cem; Kocyigit, Murat; Serin Keskinege, Bilge; Giran Örtekin, Safiye; Ozdemir, Mustafa
Abstract: Objective: In this study, we aimed to evaluate the diagnoses of the infants who were admitted to our outpatient clinic with the complaint of pulling on the ear and to identify the related factors which may contribute to the diagnosis. Methods: This prospective study included a total of 102 infants who were admitted to our hospital with the complaint of tugging and pulling on, touching, and rubbing the ears on the shoulder or pillow and shaking the head between July 2016 and July 2017. The complaints were evaluated throughout the day, and the application seasons, the person referred the patient to the ear, nose, and throat (ENT) specialist, the child development specialist and child psychiatrist, allergy and atopy histories, and the relationship between the results and diagnoses were evaluated. Results: 46.1% of the patients had normal examination findings, while the second most common finding was cerumen in 37.2%, and the third one was otitis media with effusion (OME) in 16.7%. In infants who were directly referred by the family, normal and serological diagnosis were found to be statistically significantly higher than that of OME diagnosis, whereas in the infants referred by the family physicians and pediatrist, the OME was found to be statistically significantly higher than normal and cerumen levels. The presence of additional complaints in the OME group was found to be higher than normal and cerumen group. In those with complaints during the day, the most common finding was OME, while it was cerumen in those with complaints a few times in a day and normal examination finding in those tugging on their ears only, when they were falling asleep, indicating statistical significance. Of 47 infants with normal physical examination findings, 37 were assessed by the child psychiatrist, and depression was found in six of one of the parents during the family interviews. Conclusion: In this study, the majority of the infants referred to the ENT outpatient clinic had normal examination findings, while the rate of OME diagnosis was high. Considering the negative consequences of EOM in infants, the diagnosis of the EOM becomes extremely important. If there are no otologic pathologies in the majority of infants who were admitted with ear pulling and tugging, the possibility of different factors in etiology gives rise to thought. Therefore, further studies are required to prove this condition.